Treatment use patterns in a large extended-treatment tobacco cessation program: predictors and cost implications. Issue 4 (8th January 2021) - Veldhuizen, Scott; Zawertailo, Laurie; Noormohamed, Aliya; Hussain, Sarwar; Selby, Peter
Abstract : Background: Tobacco dependence follows a chronic and relapsing course, but most treatment programmes are short. Extended care has been shown to improve outcomes. Examining use patterns for longer term programmes can quantify resource requirements and identify opportunities for improving retention. Methods: We analyse 38 094 primary care treatment episodes from a multisite smoking cessation programme in Ontario, Canada that provides free nicotine replacement therapy (NRT) and counselling. We calculate distributional measures of weeks of NRT used, clinical visits attended and total length of care. We then divide treatment courses into four exclusive categories and fit a multinomial logistic regression model to measure associations with participant characteristics, using multiple imputation to address missing data. Results: Time in treatment (median=50 days), visits (median=3) and weeks NRT used (median=8) were well below the maximum available. Of all programme enrolments, 28.8% (95% CI=28.3% to 29.3%) were single contacts, 31.3% (30.8% to 31.8%) lasted <12 weeks, 19.2% (18.8% to 19.6%) were ≥12 weeks with an 8-week interruption and 20.7% (20.3%–21.1%) were ≥12 weeks without interruptions. Care use was most strongly associated with participant age and whether the nicotine patch was dispensed at the first visit. Conclusion: Treatment use results imply that the marginal costs of extending treatment programmes are relatively low. The prevalence of single contacts supports additional engagement efforts at the initial visit, while interruptions in care highlight the ability of longer term care to address relapse. Results show that use of the nicotine patch is associated with retention in care, and that improving engagement of younger patients should be a priority.